2010
DOI: 10.1029/2010ja015335
|View full text |Cite
|
Sign up to set email alerts
|

Wave properties in the magnetic reconnection diffusion region with high β: Application of the k‐filtering method to Cluster multispacecraft data

Abstract: [1] Magnetic reconnection is a crucial physical process in laboratory and astrophysical plasmas. Plasma waves are believed to provide the dissipation mechanism in magnetic reconnection. In this paper we analyze the properties of low-frequency waves in a magnetotail reconnection diffusion region with a small guide field and high b. Using the k-filtering method on the magnetic field data measured by Cluster spacecraft, we found that low-frequency waves in the diffusion region were highly oblique propagating mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 37 publications
3
39
0
1
Order By: Relevance
“…Observationally whistler waves have indeed been detected in magnetic reconnection regions in magnetosphere plasmas where the plasma beta is on the order of unity [27,32,33]. The wave was found obliquely propagated with its wavevector nearly perpendicular to the ambient magnetic field, in a good agreement with the dispersion relation (8) [27].…”
Section: Whistler Waves In the Reconnection Layersupporting
confidence: 70%
See 2 more Smart Citations
“…Observationally whistler waves have indeed been detected in magnetic reconnection regions in magnetosphere plasmas where the plasma beta is on the order of unity [27,32,33]. The wave was found obliquely propagated with its wavevector nearly perpendicular to the ambient magnetic field, in a good agreement with the dispersion relation (8) [27].…”
Section: Whistler Waves In the Reconnection Layersupporting
confidence: 70%
“…The wave was found obliquely propagated with its wavevector nearly perpendicular to the ambient magnetic field, in a good agreement with the dispersion relation (8) [27]. The exact formula of the dispersion relation (8) was further confirmed recently by k-filter analysis for Cluster observation data [33]. It was also observed that the polarity of the wave was right-handed in the plane perpendicular to the ambient magnetic field, a typical electron mode feature [27,32].…”
Section: Whistler Waves In the Reconnection Layersupporting
confidence: 61%
See 1 more Smart Citation
“…Magnetic reconnection in the terrestrial magnetosphere has been confirmed directly by in situ observations [1][2][3][4][5]. Recently, there were many observations of reconnection in the solar wind, which were often associated with interplanetary coronal mass ejection (ICME) [6][7][8].…”
mentioning
confidence: 78%
“…The method can be used on fully coupled electromagnetic wave time series provided the proper constraints (e.g., Faraday's Law) are in place (Tjulin et al 2005(Tjulin et al , 2008. P (ω, k), the main product of the k-filtering technique, has been used in a number of studies and in a number of different ways, including determining three-dimensional dispersion relations in identifying the plasma modes that characterize fluctuations in the magnetosheath (Glassmeier et al 2001;Sahraoui et al 2003Sahraoui et al , 2004, in the high latitude magnetic cusps (Grison et al 2005), in the magnetotail in conjunction with magnetic reconnection (Eastwood et al 2009;Huang et al 2010); and in the solar wind. Three-dimensional wavenumber spectra of turbulence have been produced by integrating over the angular frequencies P (k) = P (ω, k)dω in studies of lowfrequency magnetosheath turbulence (Sahraoui et al 2006), MHD-scale turbulence in the foreshock and solar wind (Narita et al 2006(Narita et al , 2010, and kinetic-scale turbulence in the solar wind (Sahraoui et al 2010b).…”
Section: Turbulencementioning
confidence: 99%